Géza Alföldy et l’histoire des femmes dans la Rome Antique - Álvarez Melero, Anthony (Studia Europaea Gnesnensia, 2017)
The purpose of this article is to study G. Alföldy’s contribution to women’s history thanks to a review of his articles and his main monographs, so as to assess how much significance he attached to them.